Pentashihan Mushaf Al-Qur’an di Indonesia - Sudrajat, Enang (SUHUF, 2013)
In Indonesia, to keep the validity of the Quranic Mushaf is conducted in a variety of ways, among other is, the government formed the committe for the validation of the Quranic Mushaf to validate all the Mushaf that will be printed. As the guidance for the duty of the committe, the government decided the standard of the Quranic Mushaf through KMA No.25 of 1984 which was the result of the Working Consultative of the expert Muslim scholars of the Qur'an throughout Indonesia. Other efforts being conducted by the Muslim community are through Islamic boarding schools, Qur’anic study, and learning the Qur'an by heart.